Bench to bedside review: Possible role of vitamin D in autism spectrum disorder. (February 2018) - Jia, Feiyong; Shan, Ling; Wang, Bing; Li, Honghua; Miao, Chunyue; Xu, Zhida; Lin, Ching-Po; Saad, Khaled
Abstract: Autism spectrum disorder (ASD) is a group of dysfunctions in social interaction, communication, and behaviors. Studies have demonstrated that vitamin D deficiency during pregnancy and in individuals increased the risk of ASD. A genetic polymorphism study has pinpointed that genotype AA/A-allele of GC rs4588 in children is associated with ASD, which encodes the vitamin D binding protein. Translating the mentioned points into clinical practice, several clinical trials have demonstrated that vitamin D supplementation can improve the core symptoms in children with ASD. One paper also showed that possible prophylactic effect for the reoccurrence of ASD by vitamin D supplement during pregnancy and early childhood. Herein, this review aims to address the recent advances in this field and to clarify the possible role of vitamin D in ASD. Highlights: A genetic polymorphism study has pinpointed that genotype AA/A-allele of GC rs4588 in children is associated with ASD. Studies have demonstrated that vitamin D supplementation can improve the core symptoms in autistic children. This review aims to address the recent advances in this field and to clarify the possible role of vitamin D in ASD.